O continente e as 11 ilhas: a mudança institucional endógena e o lugar do Supremo Tribunal Federal na arena política - Paulo Alkmin Costa Júnior (2018)
Although studies on the field of judicial politics have early recognized the existence of an influential Federal Supreme Court, as a consequence of the generous institutional design bequeathed by the constituents of 1988, over time it seems that the role of the Court in the Brazilian political life has become one that does not resemble what has been initially described as that of "faithful servants of the regime." The perspective of this thesis is that the process through which we have advanced, over the years, towards what has been called a "Supremocracy", cannot be only explained by exogenous factors to the Federal Supreme Court, such as the high fragmentation of the political and partisan framework, or the strategic use that political actors make of the mobilization of the instruments of access to the Court. Departing from studies that focus on the evolution of institutional development, we thus seek to study endogenous institutional change, a phenomenon of subtle perception, since it depends on the exploitation by motivated agency, of spaces of interpretation in favorable contexts, with the purpose of changing, over time, the political placement of the institution to which they belong. We depart from this analytical framework in order to explain how the STF Ministers act to increase the Court's capacity to intervene in the political arena, and by extension, their own individual power. Recognizing the existence of two dimensions of understanding about the role of the STF, the macro institutional and the micro individual dimensions, we try to articulate a theoretical model that demonstrates the interaction between what we call the Islands and the Continent. In this theoretical model, the key factors are the strategic use of institutional resources at the disposal of the Ministers (such as the power to set a trial, the hearing request, and the vote anticipation), the characteristics of different compositions of the Court over time and, developing a necessary dialogue with Law, which can no longer be postponed by Political Science, the way through which what we call a "neoconstitutionalist rhetoric" influences the performance of the Supreme Court in the exercise of its main institutional resource to promote endogenous change: the judicial review. The units of analysis have been interviews conducted with STF Ministers (active and retired), the presentation of paradigmatic cases with explanatory power of the theoretically articulated framework, and the use of the QCA method (Qualitative Comparative Analysis). The latter is used to try to assess which are the necessary conditions and the set of sufficient causal conditions for the occurrence of endogenous institutional change.